2023
DOI: 10.1111/nph.18767
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pre‐ and postzygotic components of reproductive isolation between two co‐occurring Lysimachia species

Abstract: Summary Genetic divergence between species depends on reproductive isolation (RI) due to traits that reduce interspecific mating (prezygotic isolation) or are due to reduced hybrid fitness (postzygotic isolation). Previous research found that prezygotic barriers tend to be stronger than postzygotic barriers, but most studies are based on the evaluation of F1 hybrid fitness in early life cycle stages. We combined field and experimental data to determine the strength of 17 prezygotic and postzygotic reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Among sympatric Belonocnema species, multiple prezygotic barriers collectively generate near complete RI (total RI = 0.97, Egan et al 2012 a,b, Hood et al 2019, Zhang et al 2021a), whereas the strength of postzygotic barriers (hybrid inviability) is incomplete in comparison (Zhang et al 2021a). While many studies have shown that prezygotic barriers can evolve faster than postzygotic barriers and therefore play a more important role in the early stage of speciation (Orr and Coyne 1989; Coyne and Orr 1997; Mendelson 2003; Rosser et al 2019; Matute and Cooper 2021), our study provides an example where prezygotic barriers continue to be critical at the late stage of speciation (Jiménez-López et al 2023). Moreover, a common perception is that genetic divergence plays a critical role in generating postzygotic isolation via genetic incompatibility (Orr and Coyne 1989; Coyne and Orr 2004; Coughlan and Matute 2020; Matute and Cooper 2021), while ecological selection contributes more to prezygotic isolation (Funk et al 2006; Nosil 2012; Matute and Cooper 2021).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Among sympatric Belonocnema species, multiple prezygotic barriers collectively generate near complete RI (total RI = 0.97, Egan et al 2012 a,b, Hood et al 2019, Zhang et al 2021a), whereas the strength of postzygotic barriers (hybrid inviability) is incomplete in comparison (Zhang et al 2021a). While many studies have shown that prezygotic barriers can evolve faster than postzygotic barriers and therefore play a more important role in the early stage of speciation (Orr and Coyne 1989; Coyne and Orr 1997; Mendelson 2003; Rosser et al 2019; Matute and Cooper 2021), our study provides an example where prezygotic barriers continue to be critical at the late stage of speciation (Jiménez-López et al 2023). Moreover, a common perception is that genetic divergence plays a critical role in generating postzygotic isolation via genetic incompatibility (Orr and Coyne 1989; Coyne and Orr 2004; Coughlan and Matute 2020; Matute and Cooper 2021), while ecological selection contributes more to prezygotic isolation (Funk et al 2006; Nosil 2012; Matute and Cooper 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Alternatively, in the absence of divergent selection, gene flow in sympatry can erode RI by homogenizing lineages (Nosil et al 2003). Despite the importance of geography in promoting or constraining speciation (Rosser et al 2019; Jiménez-López et al 2023), many studies that have investigated ecological speciation have done so without specifically addressing and isolating its role (e.g., Via et al 2000; Nosil et al 2002; Lowry et al 2008b; Egan et al 2012a). Moreover, there is growing consensus that the completion of speciation commonly requires the evolution of multiple reproductive barriers that cumulatively reduce gene flow to near zero between diverging lineages (Ramsey et al 2003; Nosil 2007; Dopman et al 2010; Richards and Ortiz-Barrientos 2016; Lackey and Boughman 2017; Zhang et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between morph crosses in Lm produced a mean fruit-set of 47.86% ± 0.39% (n=575) and a mean number of seeds per fruit of 16.25 ± 9.16 (n=287) (Sánchez-Cabrera, 2023). Whereas in La , 100% of between morph crosses produced fruits containing 16.95 ± 7.19 seeds per fruit (n= 97) (Jiménez-López et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…25  9.16 (n=287) (Sánchez-Cabrera, 2023). Whereas in La, 100% of between morph crosses produced fruits containing 16.95  7.19 seeds per fruit (n= 97) (Jiménez-López et al, 2023).…”
Section: Reproductive Isolation Between La and Lmmentioning
confidence: 97%